Simultaneous biodegradation of bisphenol A and a biogenic substrate in semi-continuous activated sludge reactors - Ferro Orozco, Ana Micaela (2015)
In this work, the simultaneous degradation of BPA and cheese whey (CW) in semi-continuous activated sludge reactors was studied. The acclimation process and microbial growth on BPA, CW and BPA + CW were analyzed. In addition, the effect of increasing CW concentration on the BPA degradation by acclimated activated sludge was also studied. In order to reduce the factors involved in the analysis of the simultaneous degradation of BPA and CW, the effect of bisphenol A (BPA) on activated sludge not previously exposed to BPA (native activated sludge) was studied. Results demonstrate that BPA concentrations lower than 40 mg l−1 had a negligible effect on the growth of native activated sludge. In the semi-continuous reactors, the presence of CW increased the acclimation time to 40 mg l−1 of BPA. Once the capability of degrading BPA was acquired, the removal of BPA was not affected by the presence of CW. Increasing the CW concentration did not affect the removal of BPA by the acclimated activated sludge. Additionally, the CW consumption was not modified by the presence of BPA. Kinetic and stoichiometric coefficients reported in the present work can be useful in developing mathematical models to describe the simultaneous aerobic biodegradation of a biogenic substrate, such as CW, and BPA by activated sludge.